Benthic assemblages of a temperate estuarine system in South America: Transition from a freshwater to an estuarine zone - Cortelezzi, Agustina (2007)
The objectives of the present study were to describe the species composition, diversity and distribution of the zoobenthic assemblages, to estimate the abundance and biomass of the dominant species, and to identify the main environmental factors determining the distribution patterns of the invertebrates from a freshwater to an estuarine zone in a temperate estuary of South America. The Río de la Plata estuary is a microtidal system characterized by a high concentration of suspended solids. Fifty-three taxa of meso- and macro-invertebrates were identified in the samples collected during November and December 2001. Molluscs, annelids, crustaceans and nematodes were found at 90% of the sampling sites. Molluscs comprised up to about 90% of the total zoobenthos biomass: the remaining percentage corresponded mainly to annelids and less to nematodes and crustaceans. An ecocline along the salinity gradient could be observed for the benthic assemblages from the freshwater to the estuarine zone in Rio de la Plata. A Canonical Correspondence Analysis shows that results from sampling sites in the outer zone were strongly related to salinity, depth and pH and less to oxygen and percentage of clay. The results from stations in the inner zone, and part of the middle zone, were mainly related to the occurrence of sand and contents of NH4+–N, NO3−–N, and PO43−–P.